Experimental-Mathematical Modeling of Surface Moisture Removal from Pre-Moistened Seeds - F. A. Kipriyanov; A. V. Aleshkin; P. A. Savinykh (Сельскохозяйственные машины и технологии, 2025)
The paper examines the issue of excess surface moisture on seeds following pre-sowing moistening; which complicates mechanical sowing. Experimental and exploratory studies indicate that this excess moisture can be effectively removed when seeds contact a moisture-absorbing surface. (Research purpose) The study aims to provide an experimental and mathematical evaluation of the potential for removing excess surface moisture from seeds upon contact with a moisture-absorbing surface. (Material and methods) The pressing force of the caryopsis against the conveyor surface was simulated using a flat-tipped dynamometer with a force application increment of 2.5 newtons. The caryopsis was pressed against a felt fabric soaked with a dye solution. The mathematical modeling of the surface moisture removal process involved evaluating the potential for the caryopsis to roll across the surface. (Results and discussion) It was found that a randomly selected barley caryopsis with semi-axis dimensions of a = 0.001845 meters and b = 0.00146 meters in the cross-section does not achieve complete rolling but rotates by 58 degrees. At the same time; a minimum applied force of 2.5 newtons in the plane of the longitudinal section on a caryopsis with semi-axes a = 0.001845 meters and c = 0.00396 meters produces a pressing force of 0.11 newtons per square millimeter. Considering the depth of the caryopsis’s immersion in the moisture-absorbing surface and its 58-degree rotation; sufficient contact is established to remove excess surface moisture. However; in specific cases where one of the longitudinal section planes of the caryopsis has a shape approaching a diamond; the contact is incomplete. Increasing the pressing force to 0.19 newtons per square millimeter did not yield the desired effect; since the caryopsis; overcoming the resistance of the moisture-absorbing surface; made contact with the support plate. The solution was to increase the thickness of the moisture-absorbing surface to approximately half the thickness of the caryopsis. In this case; the largest contact area is ensured. (Conclusions) Experimental and mathematical evaluations established that excess surface moisture can be effectively removed from caryopses when they contact a moisture-absorbing surface with a thickness approximately half that of the caryopsis; under a pressing force of around 0.19 newtons per square millimeter.